Self-lubricating layer consist of polytetrafluoroethylene micropowders and fluorocarbon acrylate resin formation on surface of geotextile. (11th April 2018) - Long, Xiaoyun; He, Lifen; Zhang, Yan; Ge, Mingqiao
Abstract: In this study, the self-lubricating layer consist of polytetrafluoroethylene (PTFE) micropowders and two types fluorocarbon acrylate resin were formed on the surface of geotextile, to improves the evenness and decreases the frictional angle value of geotextile surface. The surface and cross section morphology of geotextile were examined by scanning electron microscopy (SEM). It was determined that composite resin emulsion was evenly coated on the surface of geotextile, to form a even and complete self-lubricating layer, and it was strongly combined with the geotextile due to formation of the transition layer. The tensile fracture stress and strain values of samples were evaluated by mechanical properties measurement, the tensile fracture stress of the untreated and treated sample was approximately 5329 kN/m and 5452 kN/m while the elongation at the yield of them was approximately 85% to 83.9%, respectively. In addition, the frictional angle values of municipal solid waste (MSW)/geotextile interface was measured by the tilt table test, the values of untreated sample was 28.1° and 24.2° under the dry and moist condition, the values of treated sample was 16.2° and 9.8°, respectively.